If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 86 + -29n = 44n Solving 86 + -29n = 44n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-44n' to each side of the equation. 86 + -29n + -44n = 44n + -44n Combine like terms: -29n + -44n = -73n 86 + -73n = 44n + -44n Combine like terms: 44n + -44n = 0 86 + -73n = 0 Add '-86' to each side of the equation. 86 + -86 + -73n = 0 + -86 Combine like terms: 86 + -86 = 0 0 + -73n = 0 + -86 -73n = 0 + -86 Combine like terms: 0 + -86 = -86 -73n = -86 Divide each side by '-73'. n = 1.178082192 Simplifying n = 1.178082192
| -2=(n-9) | | 5(2x-1)=11 | | 1.8(m+5)-(5.2+0.8m)=-7+4 | | 7/8y=-6 | | 8(x+8)=120 | | (a-3)/12=(2a+5) | | 5(-1)+8= | | 4x-a=35x-a | | 8+2m-1=9m+8-6m | | 6n-4n=-7 | | 8x-192=3x | | -4(3+5x)=108 | | 3x+x+10=10x-6x+10 | | X-4x+10=x-x | | -102=-3(-5n-6) | | 3(5b+8)=84 | | xy-4y=5x+3 | | 7+v(-3)=x+v | | -7(4+5x)=203 | | Xy+4=zforx | | 12.5/5 | | 16-1/3(24z+12)=-9z-12 | | -4(a+4)=-8-4(3a+8) | | -93=3(4k-7) | | x/10+14=12 | | -5x-10=2x+4 | | -6u-1/2=8 | | 5d-24+d(d)-65-3(d-2)=(d+3)(d+3) | | -7(6+4x)=-294 | | 5x-35=20x-5 | | 2m-n=x+4 | | 2/3(6a+3b)-1/2(a-2b) |